Compute in-Memory with Non-Volatile Elements for Neural Networks A Review from a Co-Design Perspective - Haensch, Wilfried (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2022 The Authors. Advanced Materials published by Wiley-VCH GmbH.